IMPLEMENTASI PEMBELAJARAN BERDIFERENSIASI UNTUK MENINGKATKAN KEMAMPUAN HOTS MATEMATIKA SISWA KELAS IV SD NEGERI 69 PALEMBANG - Shafa Aliyah Putri, Lily; Misdalina, Misdalina; Hidayad, Ferri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low Higher Order Thinking Skills (HOTS) in mathematics among fourth-grade students at SD Negeri 69 Palembang, particularly in solving problems requiring analysis, evaluation, and creation skills. The purpose of this study was to determine the improvement of students' mathematical HOTS after the implementation of differentiated instruction as measured by the N-Gain score. This study employed a quantitative method using a Quasi-Experimental approach with a One Group Pretest-Posttest Design. The sample consisted of 23 fourth-grade students selected through purposive sampling. Data were collected through pretests, posttests, observations, and documentation. The research instrument was a mathematics HOTS test that met validity and reliability requirements. Data were analyzed using descriptive statistics and N-Gain analysis to determine students' learning improvement. The findings revealed that differentiated instruction improved students' mathematical HOTS. The mean pretest score increased from 53.04 to 80.87 in the posttest. The N-Gain analysis indicated a moderate to high level of improvement, with a learning mastery rate of 91.3%. Differentiated instruction allowed students to learn according to their readiness, interests, and learning needs, making the learning process more effective. Therefore, the implementation of differentiated instruction had a positive effect on improving the mathematical HOTS of fourth-grade students at SD Negeri 69 Palembang.